Empowering rural students through computational thinking and real-world STEM applications: insights from an innovative high school curriculum - Li, Linlin; Huang, Chun-Wei; Morgan, Claire; Luttgen, Kim; Chow, Eunice; Yang, Shuangting (Frontiers in Education, 2025)
Rural students often face challenges receiving high-quality education in science, technology, engineering, and math (STEM). However, without meaningful STEM educational opportunities, rural students might not develop the knowledge and skills needed to compete in a technology-driven workforce. Learning by Making (LbyM), an innovative intervention funded by the U.S. Department of Education’s Investing in Innovation and Education Innovation and Research Funds, addresses gaps in STEM learning in rural settings at the early high school level by supporting teaching and learning around computational thinking and real-world STEM applications. A randomized controlled trial (RCT) in which students were randomly assigned to the treatment (received intervention) or control group (business as usual) explored the fidelity and impact of the implementation of LbyM with 9th-grade students in three rural and three high-needs high schools in California. While the quantitative analysis did not find a significant impact on student achievement, possibly due to the small sample size and the challenges of program implementation during the COVID-19 pandemic, qualitative findings highlighted several considerations for improved rural and high-needs STEM equity. For example, the LbyM’s focus on place-built students’ ability to make sense of local phenomena by applying computational thinking and coding skills and by collecting, analyzing, and interpreting data to develop solutions to problems related to their lives. Teachers reported that the focus on real-world applications increased student engagement and self-efficacy. At the same time, LbyM built teacher self-efficacy through professional learning and sharing; teachers developed computational thinking, modeling, experiment, research, and coding skills alongside their students and increased their confidence in delivering NGSS content.